Influence of nanostructure formation on the crystal structure and morphology of epitaxially grown Gd2O3 on Si(001). Issue 1 (11th February 2019) - Gribisch, Philipp; Schmidt, Jan; Osten, Hans-Jörg; Fissel, Andreas
Abstract : The epitaxial growth of Gd2 O3 on Si(001) has been investigated using several methods, including X‐ray and electron diffraction, and atomic force microscopy. The results show that crystal structure and morphology can be tuned by changing the growth conditions and are discussed within the framework of different physical effects. Abstract : The influence of growth conditions on the layer orientation, domain structure and crystal structure of gadolinium oxide (Gd2 O3 ) on silicon (001) has been investigated. Gd2 O3 was grown at low (250°C) and high (850°C) temperatures with different oxygen partial pressure as well as a temperature ramp up during growth. At low temperature, the cubic bixbyite type of crystal structure with space group was grown at low oxygen partial pressure. The layers consist of two domains oriented orthogonal to each other. The epitaxial relationships for the two domains were found to be Gd2 O3 (110)[ ]||Si(001)[110] and Gd2 O3 (110)[001]||Si(001)[ ], respectively. Applying additional oxygen during growth results in a change in crystal and domain structures of the grown layer into the monoclinic Sm2 O3 ‐type of structure with space group C 2/ m with ( ) orientation and mainly two orthogonal domains with the epitaxial relationship Gd2 O3 ( )[010]||Si(100)⟨110⟩ and a smooth surface morphology. Some smaller areas have two intermediate azimuthal orientations between these variants, which results in a six‐domain structure. The change in crystal structure can be understood based on the Gibbs–Thomson effect caused by the initial nucleation of nanometre‐sized islands and its variation in diameter with a change in growth conditions. The crystal structure remains stable even against a temperature ramp up during growth. The layers grown at high temperature exhibit a nanowire‐like surface morphology, where the nanowires have a cubic crystal structure and are aligned orthogonal to each other along the ⟨110⟩ in‐plane directions. An increase in oxygen supply results in a reduced length and increased number of nanowires due to lower adatom mobility. The results clearly indicate that both kinetic and thermodynamic factors have a strong impact on the crystal structure, epitaxial relationship and morphology of the grown layers.